2013
DOI: 10.1007/s13577-013-0060-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene analysis and dynamics of tumor stem cells in human glioblastoma cells after radiation

Abstract: Glioblastoma is the most malignant central nervous system tumor. Patients with glioblastoma are treated with a combination of surgery, radiotherapy and chemotherapy; however, this effect is not satisfactory with regard to the prognosis. It is reported that the tumor stem cells affect recurrence, and radio- and chemotherapy resistance of the tumor, and that these cells play an important role in tumorigenesis and tumor progression. Using human glioblastoma cell lines (T98G and A172), irradiated (0, 30, 60 Gy) gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…In this context, we studied CD133+ population in our cell lines before and after TMZ treatment. CD133 expression has been associated with drug resistance in SK-N-SH [ 51 ] and A172 cell lines [ 52 ]. Our results showed a significant increase in the percentage of CD133+ cells after the first TMZ cycle in A172 and LN229 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we studied CD133+ population in our cell lines before and after TMZ treatment. CD133 expression has been associated with drug resistance in SK-N-SH [ 51 ] and A172 cell lines [ 52 ]. Our results showed a significant increase in the percentage of CD133+ cells after the first TMZ cycle in A172 and LN229 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Высокая экспрессия miR-34a в клетках глиобластомы после облучения в дозе 60 Gy снижает экспрессию р53; таким образом, регуляция экспрессии miR-34a может индуцировать апоптоз даже в клетках глиобластомы, которые приобрели лучевую резистентность [106]. Несколько микро-РНК семейства let-7 были гиперэкспрессированы после облучения клеток глиобластомы линии M059K (let-7 способствует подавлению пролиферации клеток глиом), но гипоэкспрессированы в случае других клеток глиобластомы линии M059J.…”
Section: микро-рнк как прогностические маркерыunclassified
“…Recent studies in molecular biology have demonstrated the existence of cancer stem cells (CSCs) in GBM responsible for treatment failure. Despite high doses of radiation of 30–60 Gy in a single fraction, these CSCs continued to proliferate in cell cultures following radiation ( 5 ). The radio-resistance of GBM cells suggests that radiation dose escalation alone is not feasible to control tumor growth in the clinical setting because of the excessive neurotoxicity associated with such a high dose.…”
Section: Treatment Of Glioblastomamentioning
confidence: 99%